Development of E-learning Based on Augmented Reality (AR) on Reduction-Oxidation Reaction Topic - Fitriyah , Isnanik Juni; Marsuki , Muhammad Fajar; Affriyenni , Yessi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The concept of electrochemistry is based on reduction-oxidation (redox) reactions and electrolyte solutions. Where this material is difficult to understand because the aspects studied include submicroscopic aspects. It takes teaching materials that are able to display animations of redox reactions. This study aims to develop teaching materials based on Augmented Reality on Redox Reaction material. This type of research includes research and development (R&D) using the ADDIE model with the stages of analysis, design, develop and evaluation. The product will be tested for validity through expert testing and field testing. The validation test of material, media and readability experts to students resulted in a percentage of 92.5%, 94.39% and 91.6% respectively or declared very feasible and very good for use in lectures with several revisions. It can be concluded that AR-based media is stated to be very feasible and very good for use in learning. It is hoped that further testing of the effectiveness of this media will be carried out.